Limits on Estimating Autocorrelation Matrices from Mobile MIMO Measurements - Tricia J. Willink (International Journal of Antennas and Propagation)
On mobile radio links, data samples collected at successive time intervals and at closely spaced frequencies are correlated, so long data records are required to acquire sufficient independent samples for analysis. Statistical analysis of long data records is not reliable because the channel statistics remain wide-sense stationary only over short distances. This is a particular concern for MIMO systems when full autocorrelation matrices may be required for channel modelling or characterisation. MIMO channel responses from mobile measurements in an urban microcell have been used to investigate the limits on estimating autocorrelation matrices, and these are compared to those predicted by commonly used channel models.